Impact of ply arrangement on the mechanical properties of luffa cylindrica/fiberglass reinforced polyester hybrid composites - Wijang Wisnu Raharjo; Ardhana Yossa Aulia; Wibowo (BKS-TM Indonesia, 2025)
Hybrid composites are engineering materials that combine two types of reinforcing fibers to achieve superior mechanical properties. The study aims to evaluate the effect of fiber layer arrangement on the flexural strength and impact toughness of hybrid composites based on unsaturated polyester resin (UPRs) reinforced with Luffa cylindrica fibers and fiberglass. Five types of stacking configurations were tested: Luffa–Luffa (LC-LC), Luffa–chopped strand mat (LC-CSM), chopped strand mat–Luffa (CSM-LC), Luffa–woven roving (LC-WR), and woven roving–Luffa (WR-LC). Flexural testing was conducted according to ASTM D790, while impact testing followed the Izod method based on ASTM D5941. The results show that the LC-WR configuration achieved the highest flexural strength of 107.723 MPa, whereas the WR-LC configuration yielded the highest impact strength of 50.49 kJ/m². Placing the fiberglass layer on the tensile side significantly increased flexural strength, while its placement on the compressive side demonstrated superior impact energy absorption. These findings underscore the critical role of fiber stacking sequence in determining the mechanical properties of hybrid composites, which can be optimized based on specific structural application requirements.